2020
DOI: 10.1002/hbm.25161
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal functional brain network reconfiguration in healthy aging

Abstract: Healthy aging is associated with changes in cognitive performance and functional brain organization. In fact, cross‐sectional studies imply lower modularity and significant heterogeneity in modular architecture across older subjects. Here, we used a longitudinal dataset consisting of four occasions of resting‐state‐fMRI and cognitive testing (spanning 4 years) in 150 healthy older adults. We applied a graph‐theoretic analysis to investigate the time‐evolving modular structure of the whole‐brain network, by max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 87 publications
8
17
0
Order By: Relevance
“…Moreover, these intrinsic networks evolve under the effect of age toward a decrease in network segregation, as has been observed in older participants [29,63]. A recent longitudinal study [117] performed on a 4-year period showed significant reconfiguration of these networks in healthy older adults, with significant network flexibility between modules, even if the authors did not find a correlation with cognitive performance. Other studies focused on variations in the activity of the default mode network with age.…”
Section: Cognitive Aging Reserve and Compensatory Mechanismsmentioning
confidence: 86%
“…Moreover, these intrinsic networks evolve under the effect of age toward a decrease in network segregation, as has been observed in older participants [29,63]. A recent longitudinal study [117] performed on a 4-year period showed significant reconfiguration of these networks in healthy older adults, with significant network flexibility between modules, even if the authors did not find a correlation with cognitive performance. Other studies focused on variations in the activity of the default mode network with age.…”
Section: Cognitive Aging Reserve and Compensatory Mechanismsmentioning
confidence: 86%
“…However, advances in the understanding of dynamic brain networks point toward the existence of multi-scale entities in the brain architecture [1][2][3][4][5][10][11][12][13]16 . These advances followed recent developments in network science [62][63][64][65] , and generally indicate the necessity to implement unbiased methods for detecting communities [66][67][68][69][70][71][72] , possibly controlling for multiple stochasticity in the community organization, like in multi-resolution approaches 32,73,74 . In fact, the choice of the resolution parameter γ is important since it regulates the number and size of communities in a network [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…However, advances in the understanding of dynamic brain networks point toward the existence of multi-scale entities in the brain architecture [1][2][3][4][5][10][11][12][13]16 . These advances followed recent developments in network science [62][63][64][65] , and generally indicate the necessity to implement unbiased methods for detecting communities [66][67][68][69][70][71][72] , possibly controlling for multiple stochasticity in the community organization, like in multi-resolution approaches 32,73,74 . In fact, the choice of the resolution parameter γ is important since it regulates the number and size of communities in a network [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%